Evaluasi program motivator ASI mobile imogiri (MAMI) di Puskesmas Imogiri I Bantul D.I.Yogyakarta - Rini Puji Astuti; Lina Handayani; Arzani Arzani (Jurnal Cakrawala Promkes, 2019)
Background: Exclusive breastfeeding based on Government Regulation No. 33 of 2012 is breast milk given to infants since birth for six months, without adding and/or replacing with other foods or beverages (except medicines, vitamins and minerals). Nutrition improvement programs include several activities including nutritional surveillance, consultation, examination of toddlers by specialist doctors, monitoring of Exclusive Breastfeeding and Early Breastfeeding Initiation (IMD) as well as the empowerment of the Community Supporting Groups (KP-Ibu). The Imogiri (MAMI) Mobile ASI Motivator Program was formed in 2009 with its initial activities in the form of exclusive ASI mentoring activities with a background of frequent failures in exclusive breastfeeding in the first three months after the baby was born and 0-3 days the mother gave formula milk, then in the year 2015 was named as ASI Mobile Imogiri (MAMI) Motivator. Method: This study aims to determine the input, process, output, outcome, feedback and environment in the MAMI program. This research type was qualitative with a descriptive approach using an in-depth interview method and observation. This research was conducted at Puskesmas Imogiri I Bantul Special Region of Yogyakarta with 11 informants, consisting of the Program Coordinator, Head of Puskesmas, Posyandu cadre and lactating mother. Results: The number of human resources was sufficient but in quality is still said to be less. The public understands the importance of Exclusive Breast Milk, but overall the program has not run maximally. Children exclusively breastfed exclusively have better immunity than formula-fed children. The environment of breastfeeding mothers has an important role in exclusive breastfeeding. Conclusion: The program is not running maximally yet.